Fluorescence‐Lifetime Imaging and Super‐Resolution Microscopies Shed Light on the Directed‐ and Self‐Assembly of Functional Porphyrins onto Carbon Nanotubes and Flat Surfaces. Issue 41 (19th May 2017) - Mao, Boyang; Calatayud, David G.; Mirabello, Vincenzo; Kuganathan, Navaratnarajah; Ge, Haobo; Jacobs, Robert M. J.; Shepherd, Ashley M.; Ribeiro Martins, José A.; Bernardino De La Serna, Jorge; Hodges, Benjamin J.; Botchway, Stanley W.; Pascu, Sofia I.
Abstract: Functional porphyrins have attracted intense attention due to their remarkably high extinction coefficients in the visible region and potential for optical and energy‐related applications. Two new routes to functionalised SWNTs have been established using a bulky Zn II ‐porphyrin featuring thiolate groups at the periphery. We probed the optical properties of this zinc(II)‐substituted, bulky aryl porphyrin and those of the corresponding new nano‐composites with single walled carbon nanotube (SWNTs) and coronene, as a model for graphene. We report hereby on: i) the supramolecular interactions between the pristine SWNTs and Zn II ‐porphyrin by virtue of π–π stacking, and ii) a novel covalent binding strategy based on the Bingel reaction. The functional porphyrins used acted as dispersing agent for the SWNTs and the resulting nanohybrids showed improved dispersibility in common organic solvents. The synthesized hybrid materials were probed by various characterisation techniques, leading to the prediction that supramolecular polymerisation and host–guest functionalities control the fluorescence emission intensity and fluorescence lifetime properties. For the first time, XPS studies highlighted the differences in covalent versus non‐covalent attachments of functional metalloporphyrins to SWNTs. Gas‐phase DFT calculations indicated that the Zn II ‐porphyrin interacts non‐covalently with SWNTs to form a donor–acceptor complex. The covalent attachment of the porphyrin chromophore to the surface of SWNTs affects the absorption and emission properties of the hybrid system to a greater extent than in the case of the supramolecular functionalisation of the SWNTs. This represents a synthetic challenge as well as an opportunity in the design of functional nanohybrids for future sensing and optoelectronic applications. Abstract : Supramolecular and covalent assemblies can influence the morphology and optical properties of porphyrin arrays onto flat, conductive as well as insulating surfaces, and lead to the control of SWNTs (single walled carbon nanotubes) functionalisation at the nanoscale. The synthesis of new functionalised luminescent SWNTs is reported. STED super‐resolution microscopy, fluorescence‐lifetime imaging as well as XPS, TCSPC (time‐correlated single photon counting), UV/Vis, NMR spectroscopy, XRD, TEM and AFM probe the complexity of the emerging covalent and supramolecular aggregates.